The Risk Factor for Mortality in COVID-19 Patients in Mohammad Hoesin Hospital, Palembang, Indonesia (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2021)
World Health Organization (WHO) has declared the novel corona virus (COVID-19) as a pandemic due to its high transmission and the rapid spread of the COVID-19. Along these lines, there is a need for more research about risk factors that can affect the spread of COVID-19 and its fatality. Therefore, this study aims to analyze risk factors in patients who died from COVID-19 at the Mohammad Hoesin Hospital in Palembang, South Sumatra, Indonesia. This study used a cross-sectional approach. The data were collected from all patients who died with suspected, probable, and confirmed status until September 2020 Data on death due to COVID-19 were collected with suspect, probable, and confirmed status. The results showed that comorbidity became the most dominant factor (62.1%) with (OR Adj) 3.780 (1.000 – 3.168) after controlling for contact history with confirmed cases and sex. There were differences in the mean age and length of stay in patients with confirmed COVID-19 and not. Prevention of death in COVID-19 patients can be done by controlling comorbidities and contact history with positive cases of COVID-19.